Improving multi-criteria decision making algorithm for material selection - Jahan, Ali (2011)
The selection of a material for a specific engineering purpose is laborious and expensive process. Approximately always more than one material is suitable for an engineering application, and the final selection is a compromise between some advantages as well as the disadvantages. Screening and ranking are two vital steps in the material selection and variety of quantitative selection procedures have been developed to solve this issue. In this research, after classifying the current methods for screening and choosing of materials, advantages and disadvantages of the approaches were discussed. Review of literature provided evidence that the multi-criteria decision making (MCDM) approaches have the potential to greatly improve the material selection methodology. In this regard, this research focused on three problematic aspects in material selection based on MCDM as described below. Since existing tools and methods in material selection do not fully support designers during the preliminary design stages in which the designers encounter imprecise data (discrete or incomplete information) or in situations where material selection problems include intangible properties, multi-criteria decision making based on ordinal data (MCDM-BOD), which has root in linear assignment method, is proposed to rank the materials for a given engineering component. In view of the fact that many of MCDM methods require quantitative weights for the criteria and it plays a very significant role in the ranking results of the materials, a framework for determining the importance degree of criteria was presented to overcome the shortcomings of this subject in material selection. Furthermore, the suggested framework covers the situation of interdependent relationship between the criteria which has not been surveyed yet in material selection. Due to significance of compromising in material selection, VIKOR method (multicriteria optimization and compromise solution) was extended in this research. It was performed by introducing a novel normalization method to address the shortcomings of the current methods for situation in which approaching the target values of criteria is important in material selection. The proposed comprehensive version of VIKOR, not only have covered all type of criteria effectively but also have been addressed the main error of traditional VIKOR by a simpler approach. As a result, this study assists designers and engineers to make more reliable decisions in ranking stage of material selection.